A Low-FODMAP Diet Improves the Global Symptoms and Bowel Habits of Adult IBS Patients: A Systematic Review and Meta-Analysis - Wang, Jinsheng; Yang, Pengcheng; Zhang, Lei; Hou, Xiaohua (Frontiers in Nutrition, 2021)
A low fermentable oligo-, di- and monosaccharides and polyols (FODMAP) diet has been reported to be associated with improving the symptoms of irritable bowel syndrome (IBS), however, the efficacy that evaluated by different researches remains controversial. A systematic review and meta-analysis of randomized controlled trials (RCTs) was conducted to explore the efficacy of a low FODMAP diet (LFD) in alleviating symptoms of IBS. We conducted a search of the literature using the electronic databases Pubmed , EMBASE , Cochrane Central Register of Controlled Trials, and web of science for RCTs . RCTs that evaluated LFDs versus a normal diet and assessed changes of IBS symptoms were included. Data were synthesized as relative risk of global symptoms improvement, mean difference of irritable bowel syndrome related quality of life (IBS-QOL), hospital anxiety and depression scale (HADS), stool consistency/frequency, body mass index (BMI), using a random effects model. Risk of bias was assessed using Risk of Bias Tool 2 (RoB 2). Bias of publication was assessed basing on Egger’s regression analysis. Quality of evidence was assessed using GRADE methodology. A total of 10 studies were eligible for the systematic review, comparing a LFD with various control interventions in 511 participants. A LFD was associated with the improvement of global symptoms (n=390; RR=1.63; 95% CI 1.31 to 2.02; I2=39%), improvement of stool consistency (n=434; MD=-0.27; 95% CI -0.43 to -0.11; I2=19%), a reduction trend of stool frequency (n=434; MD=-0.28; 95% CI -0.57 to 0.01; I2=68%) compared with control interventions. There was no statistically significant change in IBS-QOL (n=484; MD=2.77; 95%CI -2.00 to 7.55; I2=62%), anxiety score (n= 150; MD=-0.45; 95% CI -3.38 to 2.49; I2=86%), depression score (n=150; MD=-0.05; 95% CI -2.50 to 2.40; I2=88%) and BMI (n=110; MD=-0.22; 95% CI -1.89 to 1.45; I2=14%). The overall quality of the data was “moderate” for “global improvement of IBS symptom” , “stool consistency” , “stool consistency for IBS-D” and “stool frequency for IBS-D”, and was “low” or “very low” for other outcomes according to GRADE criteria.